Features of self-taxation as a form of local budget revenues - (:unkn) unknown (DANUBE, 2022)
The aim of the article is to reveal the features of self-taxation as an independent form oflocal budget revenues. There is no consensus among domestic and foreign scholars onunderstanding the nature, place, and role of self-taxation in the system of income sources ofterritorial communities. Another problem is the fact that today in Ukraine there is virtuallyno legislative regulation of this financial and legal institution. The research methodologyis based on formal-dogmatic, comparative-legal, systemic-structural and other scientificmethods. It is substantiated that self-taxation is an independent type of mandatory payment,which is non-tax in nature and is used to address issues of local importance, the populationat a general meeting or local referendum independently determines its size, procedure forintroduction, and use.
Keywords: Self-Taxation, Tax, Local Budget Revenues, Local Government, People’s FinancialInitiative, Institution of Financial Law